Roughness parameters - Gadelmawla, E.S.; Koura, M.M.; Maksoud, T.M.A.; Elewa, I.M.; Soliman, H.H. (Journal of materials processing technology, 2002)
Surface roughness evaluation is very important for many fundamental problems such as friction, contact deformation, heat and electric current conduction, tightness of contact joints and positional accuracy. For this reason surface roughness has been the subject of experimental and theoretical investigations for many decades. The real surface geometry is so complicated that a finite number of parameters cannot provide a full description. If the number of parameters used is increased, a more accurate description can be obtained. This is one of the reasons for introducing new parameters for surface evaluation. Surface roughness parameters are normally categorised into three groups according to its functionality. These groups are defined as amplitude parameters, spacing parameters, and hybrid parameters. This paper illustrates the definitions and the mathematical formulae for about 59 of the roughness parameters. This collection of surface roughness parameter was used in a new software computer vision package called SurfVision developed by the authors. In the package, these definitions were extended to calculate the 3D surface topography of different specimens.